IDENTIFICATION OF A CLASS OF HEMOPOIETIC COLONY-FORMING CELLS FROM HUMAN UMBILICAL CORD BLOOD IN CULTURE (Iraqi Journal of Medical Sciences, 2016)
Human umbilical cord blood (UCB) contains hemopoietic stem cells (HSCs)which are regarded as valuable sources for cell transplantation.Objective:This study is aimed to identify a class of human hemopoietic colony –forming cells and found the suitable concentration for replating experiments.Methods: Cord blood (CB) was collected from placenta of newly delivered women in Al-Kadhimiya Teaching Hospital in Baghdad for normal vaginal delivery. Isolation and culturing of cells took place in Medical Research Unit College of Medicine Al-Nahrain University.The present study included two lines:- A:-Immunocytochemistry analysis of mononucleated cells (MNC s) for CD34. B:-Culturing MNCs in different concentrations in order to determine the suitable concentration for replating further experiments. Mononucleated cells were isolated by using density gradient centrifugation and the MNCs count and viability were determinated by using trypan blue.The MNCs were cultured in RPMI +10%FCS and the medium conditioned by 1%(v/v) phytohemagglutinin (PHA).The cultures were maintained in an environment of 37C?, 5%CO2 and fully humidified atmosphere for 14 days.Results: The results of immunocytochemical staining showed that MNCs were positive for CD34+,the conditioned medium gave rise to hemopoietic colonies containing colony forming unit –granulocyte-macrophage(CFUGM), burst forming colony- erythroid (BFUE)and mixed colonies(CFU-EMM).These colonies could be distinguished from other hemopoietic colonies in situ by the complete absence of signs of terminal differentiation.Conclusions: The results of this study confirmed that UCB provides a great source of hemopoietic stem cells for using in medical applications. Key words: Hemopoietic Colony-Forming Cells, Human Umbilical Cord Blood, in culture.
Keywords: Hemopoietic ColonyForming Cells; Human Umbilical Cord Blood; in culture